Collaborative learning in higher music education - Gaunt, Helena; Westerlund, Heidi (Burlington : Ashgate, 2013)
This edited collection brings together theoretical papers and case studies of practice in response to the challenge of becoming more conscious of the creative and multiple dimensions of social interaction in learning music, not least in the contemporary context of rapid change in the cultural industries and higher education as a whole.
pt. I. Theoretical perspectives and research studies -- pt. II. Practitioners' reports and narratives.
Description based upon print version of record.
English
Includes bibliographical references and index.
Description based on publisher supplied metadata and other sources.
Keywords: Music -- Instruction and study -- Psychological aspects; Education, Higher